Gestational weight gain in a migration context: are migrant women more at risk of inadequate or excessive weight gain during pregnancy?. Issue 3 (13th August 2021) - Poncet, Lorraine; Panjo, Henri; Schmitz, Thomas; Luton, Dominique; Mandelbrot, Laurent; Estellat, Candice; Andro, Armelle; Ringa, Virginie; Azria, Elie
Abstract : Background: Inadequate or excessive gestational weight gain (GWG) is associated with adverse maternal and neonatal outcomes. Little is known on adequacy of GWG in migrant women. This study investigates whether migrant women in France are at higher risk of inadequate or excessive GWG, and what characteristics are associated with GWG in migrant and non-migrant groups. Methods: We used data from the PreCARE multicentric prospective cohort (N=10 419). The study includes 5403 women with singleton deliveries, with non-migrant (n=2656) and migrant (n=2747) status. We used multinomial logistic regression, adjusting for maternal age and parity, to investigate the association of migrant status, socioeconomic status-related variables and GWG. In stratified analyses, we identified factors associated with GWG in both groups. Results: Compared with non-migrant women, migrant women had increased risk of inadequate GWG (adjusted odds ratio (aOR) 1.18; 95% CI 1.03 to 1.34). Non-migrant women with foreign origins had increased risk of excessive GWG (aOR 1.58; 95% CI 1.30 to 1.92). Women born in Sub-Saharan Africa had increased risk of both inadequate and excessive GWG. Regardless of migration status, women with lower education and women who did not start pregnancy with a normal weight were less likely to gain adequately. Inadequate prenatal care was associated with inadequate GWG only among non-migrant women. Conclusion: Migrant women are at higher risk of inadequate GWG.